Prevalence of Multidrug-Resistant Klebsiella pneumoniae Clinical Isolates in Nepal - Ranjeeta Odari; Prabin Dawadi (Journal of Tropical Medicine)
Background. Multidrug-resistant Klebsiella pneumoniae (MDR-KP) are becoming increasingly common over the world. The focus of this research was to get a quantitative assessment of K. pneumoniae and their multidrug resistance (MDR) profile in Nepal. Methods. Three electronic databases: PubMed, Google Scholar, and Research4Life were used to search publications specifying K. pneumoniae infections and/or their MDR status from January 2015 to October 2021. Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines was followed for the review, and R language 4.1.1 was used for analysis. Depending upon heterogeneity of data, we used random model for pooled data to examine the prevalence of the organism and the multidrug resistance. Results. Evaluation included 16 studies, and the pooled estimation of K. pneumoniae in total clinical samples was 3% (95% CI; 0.01–0.05). In the meta-analysis, 14 studies were combined for determining the prevalence of K. pneumoniae in total positive clinical isolates which was 16% (95% CI: 0.11–0.20), while from 12 research studies, MDR status in the pathogen was found to be 64% (95% CI, 0.53–0.74). Conclusion. The MDR status of K. pneumoniae as well as the prevalence of the bacteria in Nepal was analyzed which showed alarming situation about administration of antibiotics and indicated choosing and developing reliable antibiotic strategies.